Outcome of polymerase chain reaction (PCR) analysis in 100 suspected cases of infectious uveitis - Ranju Kharel (Sitaula); M. K. Janani; H. N. Madhavan; Jyotirmay Biswas (Journal of Ophthalmic Inflammation and Infection, 2018)
Abstract Background Polymerase chain reaction (PCR) analysis is an important tool in the diagnosis of infectious uveitis. A retrospective, interventional study of PCR analysis of ocular fluid in suspected infectious uveitis cases between January 2014 to July 2016 was done. Nested, real-time and broad range PCR was performed for detection of the genome of Mycobacterium tuberculosis, herpes virus family, Chikungunya virus, Toxoplasma gondii, fungus, eubacterium and propionibacterium acne. Results Total of 100 cases included, mean age was 39.2 ± 15.4 years. Uveitis was unilateral in 82% and granulomatous in 40%. Mean visual acuity at the initial visit and final visit was 0.73 logMar and 0.63 logMar respectively. PCR analysis confirmed the clinical diagnosis in 70.1% patients. The sensitivity, specificity, positive predictive value and negative predictive value of PCR analysis was 90.2%, 93.9%, 93.9% and 90.2% respectively. The quantitative value of real-time M. tb. Positive PCR ranged from 32c/ml to 2722 c/ml. Conclusions PCR assay is an accurate technique with high sensitivity and specificity to diagnose the DNA genome in infectious uveitis.